Gaps in the toolbox: The political upheavals in North Africa reveal deficits in EU crisis management - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2011)
Just like the rest of the international community, the European Union was caught by surprise by the events in North Africa. It was only after the former rulers of Tunisia and Egypt had been overthrown that the member states succeeded in forming a unified position vis-à-vis the developments in both countries. Now Brussels wishes to energetically support the democratic transition. Still, the planned realignment of the Union for the Mediterranean and the European Neighbourhood Policy as well as the planned trade facilitation will, at best, have an impact over the longer term. Over the short and medium run, however, the EU lacks the structures and instruments, which would enable it to contribute to conflict resolution and the containment of potential violence during the particularly critical political transition phase
Keywords: 320